LONG-LEGGED BUZZARD (AVES: BUTEO) BREEDING POPULATION FROM MOLDOVA REGION - Baltag, Emanuel Ştefan; Bolboacă, Lucian Eugen; Ion, Constantin (European Scientific Journal, ESJ, 2014)
Long-legged Buzzard (Buteo rufinus) is a medium size bird of prey which breeds in the southern Palearctic region. The known breeding area from Romania was limited to the south – eastern part (Dobrogea Region), but the available data on species distribution is very scarce. In the last 10 years, Long-legged Buzzard extended its breeding range north of this region. This northern expansion was also observed in other regions of the species‘ distribution. However, data on the new species range is almost absent. During buzzard surveys from 2011 – 2012 in eastern Romania (Moldova Region) new data was recorded on species distribution. This surveys reveals 19 breeding pairs for our study area. All the nests from Moldova Region are built in trees from small patches of forests and with a high percentage of open habitats around. The breeding pairs are not concentrated in specific places, having a homogenous distribution on the entire range of the study area. The reasons for the expansion are not yet known, but some potential factors driving it could be climate change, empty niche, habitat changing, intra- or interspecific pressure. The Long-legged Buzzard is listed in Annex I of the Bird Directive as subject of special habitat conservation measures in order to ensure survival and reproduction.